Obstetrical Management of Hydrocephalic Fetal Monster in a Tharparker Cow: A Case Report - G, Sasi; Kumar, Pramod; Kumar, Tapendra; Bhalothia, Shivendra Kumar (Indian Journal of Veterinary Sciences and Biotechnology, 2020)
Hydrocephalus condition is described either as an external or an internal. In the external hydrocephalus (Vidya Sagar et al., 2010), fluid accumulates in the subarachnoid space exterior to the brain, whereas in the internal hydrocephalus fluid accumulates in the ventricles of the brain.